Human Resource Capacity Building Through Tour Guide and Tourism Management Training - Irvan Rolyesh Situmorang; Yonson Pane; Frenky Situmorang; Sipnarong Kanchawongpaisan; Phan Bao Giang; Novi Indriyani Sitepu (Eastasouth Institute, 2025)
This community service program was conducted in Pematang Johar Village, Deli Serdang Regency, North Sumatra, which holds strong potential as a community-based tourism destination but faces challenges due to limited human resource capacity. The main objective was to enhance local residents’ knowledge and skills in tourism management and tour guiding. Using a participatory approach, the program involved three stages: observation and problem identification, training and mentoring, followed by evaluation and reflection. The program was collaboratively implemented with local government and community participation. The results indicated improved understanding of tourism management, the emergence of local tourism groups, and growing community awareness of sustainable tourism practices. Overall, this initiative strengthened local capacity toward developing Pematang Johar Village as an independent and sustainable tourism destination.